MiR‐29 coordinates age‐dependent plasticity brakes in the adult visual cortex. (7th October 2020) - Napoli, Debora; Lupori, Leonardo; Mazziotti, Raffaele; Sagona, Giulia; Bagnoli, Sara; Samad, Muntaha; Sacramento, Erika Kelmer; Kirkpartick, Joanna; Putignano, Elena; Chen, Siwei; Terzibasi Tozzini, Eva; Tognini, Paola; et al.
Abstract: Visual cortical circuits show profound plasticity during early life and are later stabilized by molecular "brakes" limiting excessive rewiring beyond a critical period. The mechanisms coordinating the expression of these factors during the transition from development to adulthood remain unknown. We found that miR‐29a expression in the visual cortex dramatically increases with age, but it is not experience‐dependent. Precocious high levels of miR‐29a blocked ocular dominance plasticity and caused an early appearance of perineuronal nets. Conversely, inhibition of miR‐29a in adult mice using LNA antagomirs activated ocular dominance plasticity, reduced perineuronal nets, and restored their juvenile chemical composition. Activated adult plasticity had the typical functional and proteomic signature of critical period plasticity. Transcriptomic and proteomic studies indicated that miR‐29a manipulation regulates the expression of plasticity brakes in specific cortical circuits. These data indicate that miR‐29a is a regulator of the plasticity brakes promoting age‐dependent stabilization of visual cortical connections. Synopsis: Ocular dominance (OD) plasticity is maximal during critical periods of development. miR‐29a expression increases during development resulting in the suppression of key regulators of plasticity, such as perineuronal nets (PNNs). miR29a putative targets are enriched for genes whose expression decreases with age, many of which are extracellular matrix and epigenetic remodeler genes miR29a upregulation during the critical period blocks OD plasticity and induces early PNN deposition miR29a downregulation in adult mice partially reverts the age‐dependent decrease of miR‐29a targets, induces weak and more permissive PNNs, and activates OD plasticity with proteomics and physiological features of juvenile mice Abstract : Ocular dominance plasticity is maximal during critical periods of development. miR‐29a expression increases during development resulting in the suppression of key regulators of plasticity, such as perineuronal nets.